INNER CORE ATTENUATION ANISOTROPY - Yu W.C.; Wen L. (My University, 2006)
We investigate the attenuation structure of the Earth's inner core and its relationship to the velocity structure globally and along various sampling directions, by studying the amplitude ratios and the differential travel times of the PKiKP-PKIKP and PKPbc-PKIKP phases. Our observations reveal that the amplitude ratios of these core phases, like the differential travel times, vary in both sampling direction and geographic location, and the correlation is ubiquitous between small (large) PKIKP/PKiKP or PKIKP/PKPbc amplitude ratios and large (small) differential PKiKP-PKIKP or PKPbc-PKIKP travel times. These observations indicate that the Earth's inner core is anisotropic in attenuation, and the direction of high (low) attenuation corresponds to that of high (low) velocity. Such anisotropic behaviors can be explained by different alignments of the hexagonal close-packed (hcp) iron crystals under the hypothesis that the hcp iron crystals are anisotropic in attenuation with their axis of high (low) attenuation corresponding to that of high (low) velocity. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANISOTROPY; ATTENUATION STRUCTURE; EARTH'S INNER CORE; HEXAGONAL CLOSE-PACKED IRON; VELOCITY STRUCTURE